2017
DOI: 10.1108/ijwbr-01-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Using push-pull winescape attributes to model Australian wine tourist segmentation

Abstract: Purpose The study aims to introduce a comprehensive segmentation instrument that incorporates the push–pull winescape attributes, providing a new perspective of the wine tourist profile and explaining their behavioural intentions in the Australian winescape. Design/methodology/approach A literature review, focus groups and expert panels generated an extensive list of push–pull winescape attributes. Pen-and-paper surveys conveniently sampled 739 wine tourists at three wineries across three wine regions in Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 55 publications
(93 reference statements)
0
23
0
Order By: Relevance
“…Gender has long been considered as one of the core socio-demographic variables that affect consumer decision and purchasing behaviors [5,15,45]. Male and female customers show a different level of preference [16], product performance assessment [5], satisfaction [14,15], and behavioral intentions [46] in product/service consumption situations. Male and female patrons also show a different attitude toward the product and its attributes [14,45].…”
Section: Gender and Its Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender has long been considered as one of the core socio-demographic variables that affect consumer decision and purchasing behaviors [5,15,45]. Male and female customers show a different level of preference [16], product performance assessment [5], satisfaction [14,15], and behavioral intentions [46] in product/service consumption situations. Male and female patrons also show a different attitude toward the product and its attributes [14,45].…”
Section: Gender and Its Effectmentioning
confidence: 99%
“…In addition, even though the green physical environment has been researched in previous studies, the gender differences in the context of visitors' loyalty intention formation has rarely been explored in the airport industry. According to recent studies [5,[14][15][16], gender difference in travelers' consumption behaviors and the loyalty generation process for tourism products is apparent. Despite this evidence, the effect of gender on the relationship between airport users' perception regarding a green physical environment and the cognitive/affective/conative responses have hardly been examined.…”
Section: Introductionmentioning
confidence: 99%
“…The latest studies addressing the influence of external parameters on wine tourist behaviour such as winescape (Quintal et al, 2015), in combination with the characteristics of wine tourist, using the knowledge for segmentation of the wine tourist (Quintal et al, 2017) such as: specific cultural and geographic (Charters, Ali-Knight 2002), values reflecting on their extrovert and hedonistic lifestyle (Simpson, Bretherton, 2004), destinations offering a wide range of cultural and outdoor attractions (Getz, Brown, 2006) or level of consumer involvement, where four groups of involvement were identified -low-involvement wine tourists, highly involved wine tourists, interestdriven wine tourists, and high-risk perception wine tourists (Gu et al, 2018). Sekulic et al (2017) have monitored Serbian's wine regions and had identified two types of wine tourists -active (consuming wine and visiting winery) and potential (consuming wine).…”
Section: Literature Overviewmentioning
confidence: 99%
“…This special issue also examines several provider issues such as benchmarking (Terziyska, 2017), signage (Byrd et al, 2017b) and the strategic profiling of wineries and value contribution of individual tourism activities (Dressler, 2017). Quintal et al (2017) use the dominant motivational framework of push and pull attributes to segment the Australian wine market. Despite the use of this framework extensively in tourism studies to understand the motivation of pleasure travellers (Prayag and Hosany, 2014), its application for segmentation purposes in the wine tourism context remains limited.…”
Section: Johan Bruwer Editor-in-chiefmentioning
confidence: 99%
“…content analysis and survey) and quantitative methods (e.g. PLS-SEM) to explore a range of psychological and marketing concepts such as motivation (Quintal et al, 2017); brand personalities (Morrish et al, 2017); involvement, emotions and attachment (Santos et al, 2017); wine prestige and relationship quality (Loureiro and da Cunha, 2017); and the value attached by consumers to different information sources (Byrd et al, 2017a). This special issue also examines several provider issues such as benchmarking (Terziyska, 2017), signage (Byrd et al, 2017b) and the strategic profiling of wineries and value contribution of individual tourism activities (Dressler, 2017).…”
Section: Johan Bruwer Editor-in-chiefmentioning
confidence: 99%